2001
DOI: 10.2135/cropsci2001.1931
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective DNA Marker Assessment of the Development of Insect Resistant Soybean

Abstract: characteristics (Lambert and Tyler, 1999). The lack of development of superior SIR cultivars may be due to There has been limited success over the past 30 yr in the developthe quantitative nature of resistance and to the retention ment of superior soybean cultivars [Glycine max (L.) Merr] with of undesirable PI donor alleles affecting any number insect resistance. Success may be hampered by the quantitative nature of resistance and by linkage drag from resistant plant introduction of traits because of their ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 25 publications
1
45
0
6
Order By: Relevance
“…In addition, three QTLs for antibiosis resistance have been detected from the three resistant cultivars, one located in linkage group (LG) M has been suggested to be associated with antixenosis resistance by its location in LG-M (Rector et al 2000). Narvel et al (2001) reported that at least 13 of the 15 insect-resistant cultivars developed from Sodendaizu have the allele of Sodendaizu on the QTL of LG-M, and the locus is tightly linked to the simple sequence repeat (SSR) marker Satt536. Narvel et al (2001) inferred that the QTL on LG-M had a considerable effect but the other QTLs on LG-D1b, G and H had minor effects or no effect, from the genotypes of the SSRs flanking the QTL in the 15 insect-resistant cultivars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, three QTLs for antibiosis resistance have been detected from the three resistant cultivars, one located in linkage group (LG) M has been suggested to be associated with antixenosis resistance by its location in LG-M (Rector et al 2000). Narvel et al (2001) reported that at least 13 of the 15 insect-resistant cultivars developed from Sodendaizu have the allele of Sodendaizu on the QTL of LG-M, and the locus is tightly linked to the simple sequence repeat (SSR) marker Satt536. Narvel et al (2001) inferred that the QTL on LG-M had a considerable effect but the other QTLs on LG-D1b, G and H had minor effects or no effect, from the genotypes of the SSRs flanking the QTL in the 15 insect-resistant cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Narvel et al (2001) reported that at least 13 of the 15 insect-resistant cultivars developed from Sodendaizu have the allele of Sodendaizu on the QTL of LG-M, and the locus is tightly linked to the simple sequence repeat (SSR) marker Satt536. Narvel et al (2001) inferred that the QTL on LG-M had a considerable effect but the other QTLs on LG-D1b, G and H had minor effects or no effect, from the genotypes of the SSRs flanking the QTL in the 15 insect-resistant cultivars. By using a backcrossed line, the QTL on LG-M derived from Sodendaizu was confirmed to have a detrimental effect on the development of lepidopteran larvae and defoliation by them (Walker et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Antibiosis was evaluated using the pupal weight and duration from hatching to pupation of CCW reared on detached soybean leaves 39 . Antixenosis was evaluated by comparing the leaf area consumed in a susceptible line versus an evaluated line when CCW larvae were free to choose between the leaves in a petri dish 37 .…”
Section: Development Of Methods For Evaluating Insect Resistance Andmentioning
confidence: 99%
“…Narvel et al 39 found that PI229358 and PI171451 alleles were conserved in most insect-resistant lines developed by traditional cross-breeding. Walker et al 51,52 confirmed the effect of the QTL in antixenosis and antibiosis using near-isogenic lines derived from PI229358.…”
Section: Validation Of Insect Resistance Qtlsmentioning
confidence: 99%
See 1 more Smart Citation